Responsabilidade e heurística do temor: acerca da ética de Hans Jonas - Fortes, Esmelinda Silva (2014)
We assume, as object of work, a new proposal ethical theory developed by the German philosopher Hans Jonas(1903-1993). Concerned about the catastrophic direction that techno-scientific civilization seems to be taking Jonas in his Principle Responsibility (1979) unveils the problems engendered by excessive use of the technique. Thus, this work reveals itself as crucial to the development of this work reflection. At first, we will consider in addressing the issue of imbricated technique technological society, through the allegorical figure of Prometheus unchained, traveled the implications of baconian program assumed domination of nature in the modern era, returning to the influence of estocisimo, to a reformulation of Kantinian impertive given the changes for which contemporary ethics is submitted. On the second point, the question of life ontology highlights the need to recognize the intrinsic value of being organic, ethical thinking beyond anthropocentrism; to recognize the man not only as modifier of nature, but also as an object of their own involvement, reflecting the extent to which the man of the technological society still retains his human essence. Finally, the third phase houses the heuristic method assumed as fear, thinking the responsibility as a political, ethical and collective principle, but above all, a commitment to future generations